Moving off the Map: How Knowledge of Organizational Operations Empower s and Alienates - Huising, Ruthanne (Organization Science, 2019)
This paper examines how employees become simultaneously empowered and alienated by detailed, holistic knowledge of the actual operations of their organization, drawing on an inductive analysis of the experience s of employees working on organizational change teams. As employees bu ild and scrutinize process maps of their organization, they develop a new comprehension of the structure and operation of their organization . What they had perceived as purposively designed, relatively stable, and largely external is revealed to be continuously produced through s ocial interaction. I trace how this altered comprehension of the organ ization’s functioning and logic changes employees' orientation to and place within the organization. Their central roles are revealed as les s efficacious than imagined and, in fact, as reproducing the organizat ion's inefficiencies. Alienated from their central operational roles, they voluntarily move to peripheral change roles from which they feel empowered to pursue organization-wide change. The paper offers two con tributions. First, it identifies a new means through which central act ors may become disembedded, that is, detailed comprehensive knowledge of the logic and operations of the surrounding social system. Second, the paper problematizes established insights about the relationship be tween social position and challenges to the status quo. Rather than a peripheral social location creating a desire to challenge the status q uo, a desire to challenge the status quo may encourage central actors to choose a peripheral social location.
Keywords: agency; alienation; business process redesign; change agents; embeddedness; organizational change; social position